Hematological parameters of boars fed with complex feed additives under heat stress conditions - I. T. Ivanytskyi; M. M. Sharan (Біологія тварин)
The aim of the work was to determine the effect of feeding complex feed additives on hematological indicators of boars under conditions of heat stress and normal temperature. The experiment was conducted on nine clinically healthy breeding boars aged 2–4 years of the Landrace, Piétrain and Maxter breeds. Two series of experiments lasting 90 days were conducted with the similar study of animals, material selection and analysis: under normal thermal conditions (<23°С) and under conditions of heat stress (25–30°С). In the first series (Experimental group 1), all boars were individually given a feed additive in the form of a liposomal emulsion, which contained vitamins A, D3, E, and C with zinc gluconate in a dose of 2 ml, for 30 days. In the second series of experiments (Experimental group 2), all boars were individually given a feed additive in the form of a liposomal emulsion, which contained vitamins A, D3, E, C, zinc gluconate and betaine in a dose of 20 ml, for 30 days. Heat stress was simulated by creating conditions of elevated temperature (25–30°С) and humidity (70–80%) 3 hours daily for 7 days by insulating the cages with polyethylene film. Temperature and humidity were monitored with a thermohygrometer with average values determined at each stage. At the end of each stage of the experiment, blood samples were taken from all experimental boars and hematological parameters (erythrocytes, hemoglobin, hematocrit, erythrocyte indices, platelet and leukocyte content) were determined. It has been found that under the influence of heat stress in boars, hematological indicators significantly (P<0.05–0.001) decrease: the content of erythrocytes, hemoglobin, hematocrit, MCV, MCHC with a slight decrease in the content of leukocytes and platelets compared to the period of normal temperature conditions. Feeding boars vitamins A, D3, E, and C with zinc gluconate under heat stress conditions caused a significant (P<0.05–0.01) increase in the content of erythrocytes, leukocytes, hemoglobin, hematocrit, erythrocyte indices MCV and MCH, compared to the control. Similarly, feeding boars with vitamins A, D3, E, C, zinc gluconate and betaine under heat stress conditions resulted in a significant (P<0.01) increase in the content of erythrocytes, leukocytes, hemoglobin and hematocrit with a simultaneous increase in the erythrocyte indices MCV, MCH (P<0.05) and MCHC. At the same time, feeding boars with both complex feed additives under normal temperature and humidity conditions caused a slight increase in all studied hematological parameters.